DESIGN THINKING APPROACH IN VIRTUAL LEARNING ENVIRONMENTS: TRENDS, IMPACTS, AND CHALLENGES - Nurzaelani, Mohammad Muhyidin; Wibawa, Basuki; Supriadi, Dedi; Yanti, Fitri; Andanari, Runi (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2026)
The digital transformation in education has opened up new opportunities to create more interactive, personalized, and flexible learning experiences. One pedagogical model that is currently receiving attention is the Design Thinking (DT) approach. However, the virtual format itself has the potential to undermine one of the main principles of the DT model, namely the experience-based principle. As interest in the application of DT in virtual learning contexts increases, several studies have attempted to examine its effectiveness, learning outcomes, and barriers encountered. The results of a systematic literature review indicate that the application of the DT approach in a Virtual Learning Environment (VLE) is not only possible but also has the potential to accelerate the transformation of education towards a more collaborative, human-centered, and solution-oriented model. However, its success depends on technological readiness, facilitator capabilities, and pedagogical innovation. The results of a systematic literature review show that the DT approach is effective in increasing engagement and motivation to learn even in VLEs. This approach is able to create a more active, collaborative, and meaningful learning experience, even in online and asynchronous situations. Virtual collaboration can be creatively facilitated through the DT structure. Even without physical meetings, the DT process can still be carried out effectively with the support of digital technology and appropriate learning methods.